Case report of a ruptured right atrial aneurysm in a child and a comprehensive literature review - Zhou, Jie; Xin, Hao; Li, Qiao; Zhu, Mei (Frontiers in Pediatrics, 2024)
Background: The right atrial aneurysm is a rare cardiac malformation of unknown origin. It is typically asymptomatic but can occasionally lead to life-threatening and serious complications. Case Description: We present a case of a right atrial aneurysm in an eight-year-old child who experienced complications including rupture of the atrial aneurysm, thrombosis, and recurrent large pericardial effusions over a one-month period. Following surgical treatment, the child had a favorable prognosis. Conclusion: A congenital right atrial aneurysm may manifest as either a widespread enlargement of the right atrium or a localized, smaller sac-like protrusion. In the latter case, diagnosis can be challenging to confirm through transthoracic echocardiography alone, and may require a cardiac computed tomography angiography examination for a definitive diagnosis. For patients experiencing recurrent large volumes of bloody pericardial effusion within one month, and exhibiting no atrial enlargement but showing abnormalities of the atrial wall in echocardiography, it is important to be vigilant about the potential for atrial aneurysm rupture in the heart. Timely treatment is essential to prevent the progression of the condition, which could result in a poor prognosis.